A phrase-didactic look at Italianness. How learning the Italian collocations of colors can help to discover the Italian mentality - Gadacz, Joanna (Doświadczanie i wyrażanie włoskości: Aspekty językoznawcze i glottodydaktyczne, 2021)
This paper describes the definitions of collocations and their classification. It presents the utility of collocations in the didactic context, the analysis of the lexical exercises in the Italian textbooks for foreign students and it examines the colour collocations based on the concept of mentalità.